Plurality of epistemic collections in the Amazon: history, management and challenges of the Curt Nimuendajú Archaeology Lab (UFOPA) - Jácome, Camila (2020)
Archaeological collections constitute relevant heritage and study sources, essential for understanding the historical and cultural legacy promoted by past and present societies. The management of these collections goes beyond their curatorship, implying also ethical, political, educational and scientific commitments vis-à-vis different communities. Within this scenario, UFOPA’s Curt Nimuendajú Archaeology Lab, situated in Santarém, Pará presents a special configuration due to its location and because it is accessed by different actors, including indigenous and traditional peoples. The lab acts as locus for generational connection and plural knowledge. Based on these specificities, we present the trajectory of its creation and of the constitution of its collections, in addition to the challenges inherent to its management.